Improving Expository Writing Ability with TTW-YouTube Approach: A Case Study at SMAN 1 Ngronggot - Suryaningsih, Sukmawati Adi; Pitoyo, Andri; Rahmayantis, Marista Dwi (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Lack of understanding of expository text writing material causes students to have difficulty in writing expository texts. One of the difficulties faced is that students have difficulty developing ideas. This can be caused by the lack of variety in the use of learning models. The purpose of this study is to describe the effect of Think Talk Write (TTW) model assisted by YouTube videos on writing exposition texts of class X students of SMAN 1 Ngronggot in Nganjuk Regency. The data collection technique was done by using exposition text writing test. The data processing used SPSS version 29.0, by conducting a pre-requisite test, namely normality and homogeneity tests then continued with the Independent samples test. The research employed a quasi-experimental method using a pretest-posttest control group design. The study sample consisted of 71 students, who were assigned to two groups: an experimental class and a control class. The result of this study is that there is a positive effect of using the TTW model assisted by YouTube videos on writing exposition text, with the results of the hypothesis test obtaining a sig (2-tailed) value of 0.002 ˂ 0.05.